Anemone pindariensis (Ranunculaceae), most recently described from the western Himalaya in India, is a teratological form of A. rivularis - Fei, Wen-Qun; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2022)
Based on literature survey and observations on herbarium specimens and living plants in the wild, we demonstrate that Anemone pindariensis (Ranunculaceae), most recently described from the western Himalaya in India, is a teratological form of A. rivularis. We therefore place the former in synonymy with the latter herein.